Biocompatible ultrananocrystalline diamond coatings for implantable medical devices. (15th July 2014) - Auciello, Orlando; Gurman, Pablo; Guglielmotti, Maria B.; Olmedo, Daniel G.; Berra, Alejandro; Saravia, Mario J.
Abstract